Performance Evaluation of Warm Mix Asphalt Mixtures with Recycled Asphalt Pavement - Sengoz, Burak; Topal, Ali; Oner, Julide; Yilmaz, Mehmet; Dokandari, Peyman Aghazadeh; Kok, Baha Vural (Budapest Univ Technology Economics, 2017)
Warm mix asphalt (WMA) technology provides not only the production of asphalt pavement at a lower temperature than the temperature maintained in Hot Mix Asphalt (HMA) but also encourages the utilization of Recycled Asphalt Pavement (RAP) and therefore saves energy and nonrenewable resources as well as reduces emissions and fuel consumption. This paper describes the feasibility of utilizing four different WMA additives (organic, chemical, synthetic zeolite and natural zeolite) with different rates of RAP. Following the determination of optimum RAP content corresponding to each WMA additive, Marshall analysis, indirect tensile stiffness modulus and fatigue behavior of HMA and WMA involving RAP were analyzed and compared with control specimens. Hamburg wheel tracking device was also utilized to evaluate the permanent deformation characteristics of mixtures containing optimum RAP content.
Keywords: warm mix asphalt; recycled asphalt pavement; indirect tensile stiffness modulus; fatigue behavior; Hamburg wheel tracking device